Perlindungan Hukum Terhadap Pemegang Saham Perseroan Terbatas Hasil Konsolidasi - Setiawati, Yeyen; Sudiarto (Commerce Law, 2024)
The aim of this research is to determine the regulations for shareholders of consolidated limited liability companies in positive law in Indonesia and to determine the legal protection for minority shareholders of consolidated limited liability companies. The type of research used in this research is normative legal research using a statutory approach and a conceptual approach. In limited company consolidation in Indonesia, Law Number 40 of 2007 regulates shareholders by regulating their election, rights and obligations. Shareholders have rights such as attending the GMS, receiving dividends, and being involved in important company decisions. These rights relate to ownership, including distribution of dividends and liquidation of assets.